Interaction of Management and Economics in Improving the Efficiency of the Development of the Sports Industry - Lianna Samvel Abrahamyan (Indonesian Journal of Sport Management, 2023)
Summing up, the conducted research outlines the major role of interdisciplinary approach towards enduring efficient development in sports sector. Such an approach is rooted in modern challenges of fast-changing environment in both exogenic and endogenic aspects of sport industry. Consequently, such a situation needs an adequate toolkit in the form of interdisciplinary organizational model aimed at supporting value-focused development.